Sensitivity of the Baroreceptors and the State of the Autonomic Nervous System in Patients with Chronic Impairment of Consciousness Due to Severe Brain Damage - V. N. Dorogovtsev; D. S. Yankevich; A. L. Parfenov; A. E. Skvortsov; A. V. Kotelnikova (Общая реаниматология)
Purpose of the study: to examine sensibility of baroreceptors and the autonomic nervous in the passive orthostatic test in patients with chronic impairment of consciousness due to severe brain damage and determine their role in the rehabilitation process.Materials and methods. The study included 30 patients with long-term impairment of consciousness due to severe brain damage (group 1), 10 of them being in the vegetative state (VS) and 20 being in the minimally conscious state (MCS). Craniocerebral trauma was the main cause of severe damage in that group (53% of patients). The comparison group included 24 patients with focal neurological symptoms caused predominantly — 79.2% of cases — by cerebrovascular disorders (group 2). The control group (group 3) consisted of 22 healthy volunteers of a comparable age. All measurements were done with the help of a Task Force Monitor 1030i (CNSystem, Austria) in the course of passive orthostatic test at 0°–30°–60°–0°. Changes in the power of low-frequency (LFS) and highfrequency spectrum (HFS) of heart rate variability and baroreceptors sensibility (BRS) were analyzed. Statistical analysis was carried out using Statistica-10 software. Significance of inter-group differences on unrelated samples was determined by the Mann–Whitney U-test. Differences between groups were considered significant at P 0.05.Results. Maximal background values of BRS were found in the control group. In group 1 and 2 patients, considerable decrease of that index was noted, which was proportional to the brain damage severity. Similar dynamics was observed for the indices of autonomic nervous system sensibility (LFS and HFS). The main trend of orthostatic changes of BRS, LFS, and HFS was characterized by progressive decrease of the indices with increase of the patients’ angle of tilting and their return to the baseline level after the patients were put back into the horizontal position. 4 patients of group 1 (14%) displayed signs of orthostatic disorders upon tilting to 30°: in 3 cases, orthostatic hypotension was observed, and in one case the postural orthostatic tachycardia syndrome (POTS) was diagnosed. Those patients differed by lower BRS and higher sympathetic system activity (LFS) vs. the same indices of other patients in that group.Conclusion. Patients with chronic impairment of consciousness during the post-comatose period after a severe brain damage display a significant decrease of baroreceptors sensibility and autonomic nervous system disorders manifesting in significantly lower activity of the sympathetic and parasympathetic systems. The prominence of such disorders is associated with brain damage severity. Their risk of developing orthostatic hypotension during tilting towards a vertical position is higher in patients who have lower baroreceptors sensibility, and this should be taken into account beginning the process of their verticalization.